Lipid accumulation product and visceral adiposity index for incidence of cardiovascular diseases and mortality; results from 13 years follow‐up in Isfahan cohort study - Mohammad Fakhrolmobasheri; Amir Parsa Abhari; Maryam Heidarpour; Saina Paymannejad; Mahsa Pourmahdi‐Boroujeni; Amir Sepehr Saffari; Paria Okhovat; Hamidreza Roohafza; Masoumeh Sadeghi; Najmeh Rabanipour; Davood Shafie; Nizal Sarrafzadehgan (Wiley, 2024)
Abstract Background /Aims: Visceral adiposity index (VAI) and lipid accumulation product (LAP) are novel anthropometric indices that have shown an association with metabolic syndrome; however, limited data are available regarding the predictive performance of these indices for the incidence of cardiovascular diseases (CVD) and mortality. Methods This study was performed on the data retrieved from Isfahan Cohort Study (ICS). ICS is an ongoing population‐based cohort study conducted in 3 counties in central Iran. Pearson correlation analysis was performed between LAP, VAI, and metabolic parameters. Cox regression analysis and receiver operative characteristics (ROC) curve analysis were performed in order to evaluate the ability of VAI and LAP for the incidence of CVD, CVD‐associated mortality, and all‐cause mortality. We further compared the predictive performance of VAI and LAP with body mass index (BMI). Results LAP and VAI were significantly correlated with all metabolic variables, including blood pressure, fasting blood glucose, and lipid profile components. Univariate regression analysis indicated a significant association between LAP and VAI and CVD incidence. In multivariate analysis, only VAI was significantly associated with CVD incidence. Regarding CVD mortality, only VAI in the multivariate analysis revealed a significant association. Interestingly, Both VAI and LAP were negatively associated with all‐cause mortality. ROC curve analysis indicated the superior performance of LAP and VAI for predicting CVD incidence compared to BMI; however, BMI was better in predicting all‐cause mortality. Conclusion Compared to BMI, LAP and VAI have better predictive performance for the incidence of CVD. In contrast, BMI was superior to VAI and LAP in the prediction of all‐cause mortality.